2011
DOI: 10.5194/acp-11-13269-2011
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal variation of CCN concentrations and aerosol activation properties in boreal forest

Abstract: Abstract. As a part of EUCAARI activities, the annual cycle of cloud condensation nuclei (CCN) concentrations and critical diameter for cloud droplet activation as a function of supersaturation were measured using a CCN counter and a HTDMA (hygroscopicity tandem differential mobility analyzer) at SMEAR II station, Hyytiälä, Finland. The critical diameters for CCN activation were estimated from (i) the measured CCN concentration and particle size distribution data, and (ii) the hygroscopic growth factors by app… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
137
6

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 131 publications
(162 citation statements)
references
References 74 publications
19
137
6
Order By: Relevance
“…In their study, the particle hygroscopicity showed no obvious size dependency and was higher than our observation in Beijing. In contrast, κs measured were relatively low at a forested site in Colorado (κ = 0.16 ± 0.08 detected by CCN counter (CCNc)), a boreal forest in Finland (κ = 0.18 at RH = 90 %) (Sihto et al, 2011), and a tropical forest site in the Amazon (κ = 0.16 ± 0.06 detected by CCNc) (Gunthe et al, 2009). At these forested locations, organic species were predominant in particles.…”
Section: Overview Of Particle Hygroscopic Growth and The Mixing Statementioning
confidence: 76%
“…In their study, the particle hygroscopicity showed no obvious size dependency and was higher than our observation in Beijing. In contrast, κs measured were relatively low at a forested site in Colorado (κ = 0.16 ± 0.08 detected by CCN counter (CCNc)), a boreal forest in Finland (κ = 0.18 at RH = 90 %) (Sihto et al, 2011), and a tropical forest site in the Amazon (κ = 0.16 ± 0.06 detected by CCNc) (Gunthe et al, 2009). At these forested locations, organic species were predominant in particles.…”
Section: Overview Of Particle Hygroscopic Growth and The Mixing Statementioning
confidence: 76%
“…A peak in aerosol hygroscopicity is observed around midday when D c reaches its minimum. Several previous studies have reported such behaviour in Hyytiälä and have attributed it to the vegetation activity, photochemistry and the ageing of organics during sunlight hours (Sihto et al, 2011;Cerully et al, 2011;Paramonov et al, 2013). While no diurnal pattern of aerosol hygroscopicity is visible for Jungfraujoch for winter and spring, a very clear pattern does exist in the summer and autumn.…”
Section: Ccn and Their Hygroscopicitymentioning
confidence: 83%
“…κ CCNc for all particle sizes reaches a maximum within 1-2 h of local noon, suggesting that photochemical processes are dominant at that time, which is consistent with the peak in oxygenated organic aerosol mass (Aiken et al, 2009) and water soluble organic carbon mass (Hennigan et al, 2008) observed during the daytime at the T0 and T1 sites, respectively. New particle formation (NPF) events occurred frequently during MIRAGE 2006(Smith et al, 2008, as illustrated by the particle size distributions (Fig. 2f).…”
Section: Diurnal Changes In Aerosol Hygroscopicitymentioning
confidence: 99%
“…The colder end of the CCN column was maintained at T c = 24.0 ±1.38 • C, while the warmer end was maintained at T h to obtain T ranging from from 1.87±0.032 • C to 13.7 ± 0.038 • C, corresponding to a range of supersaturations ∼ 0.07-1.15 %. For reference, ambient cloud supersaturations are generally <1 % (Seinfeld and Pandis, 1998). Supersaturation in the CCNc was calibrated in the field using atomized and classified NaCl particles, which were also used to simultaneously calibrate the HTDMA system.…”
Section: Measurements and Instrumentationmentioning
confidence: 99%